Diversity patterns of plants and arthropods in soybean agro-ecosystems in the Grassland Biome of South Africa - Paul Duvel Janse van Rensburg; Stefan John Siebert; Tlou Masehela; Suria Ellis; Johnnie Van den Berg (Society for Indonesian Biodiversity, 2020)
Abstract. Janse van Rensburg PD, Siebert SJ, Masehela T, Ellis S, Van den Berg J. 2020. Diversity patterns of plants and arthropods in soybean agroecosystems in the grassland biome of South Africa. Biodiversitas 21: 5559-5570. Soybean is widely cultivated in the grassland biome of South Africa (ca.  800 000 ha per annum). Yet the possible effects that large-scale cultivation of soybean has on biodiversity in adjacent habitat are not fully understood. This study aimed to describe the plant and arthropod species assemblages and diversity patterns within these soybean agroecosystems. Surveys were conducted inside soybean fields, field boundaries (transition zones between soybean fields and adjacent habitat), and adjacent pasture. An adapted D-vac was used to sample arthropods in the different zones, while plant surveys were conducted by means of fixed width (2 m) line transect. A total of 320 plant species (4910 specimens) and 373 arthropod morpho-species (9216 specimens) were recorded. Soybean fields had significantly lower plant and arthropod diversity than the adjacent habitats. Plant species diversity was similar in the field boundary and adjacent pasture. Significantly higher species richness and abundance of arthropods were found in the boundary than the pasture. These results show that the cultivation of soybean and the associated agricultural practices had no adverse effects on biodiversity patterns in the adjacent habitats. However, the boundary dominated by alien plant species did contain a significantly different plant species composition from the pasture. This difference was also mirrored by unique assemblages of arthropods. This suggests that disturbance resulting from soybean cultivation contributed to species losses and gains that maintained diversity in the field boundary but changed its plant and arthropod species composition. No effect was found in the pasture beyond the boundary (> 50 m). High diversity, but unique species assemblages of plants and arthropods in the boundary and pasture suggest that these habitats may have important conservation value in soybean agroecosystems by supporting ecosystem functions and services.